2014
DOI: 10.1088/0953-8984/26/6/064213
|View full text |Cite
|
Sign up to set email alerts
|

Inspired by nature: investigating tetrataenite for permanent magnet applications

Abstract: Chemically ordered L10-type FeNi, also known as tetrataenite, is under investigation as a rare-earth-free advanced permanent magnet. Correlations between crystal structure, microstructure and magnetic properties of naturally occurring tetrataenite with a slightly Fe-rich composition (~ Fe55Ni44) obtained from the meteorite NWA 6259 are reported and augmented with computationally derived results. The tetrataenite microstructure exhibits three mutually orthogonal crystallographic variants of the L10 structure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
88
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 22 publications
9
88
1
Order By: Relevance
“…2,7 Therefore, the ordered phase of FeNi has drawn renewed attention as a novel alternate to rare earth based permanent magnets. [8][9][10][11] The theoretical maximum magnetic energy product of L1 0 FeNi (∼42 MGOe) is close to that of the currently available best hard magnets. 10,11 It is to be noted that the tetrataenite (L1 0 FeNi phase) was formed during extremely slow cooling of billions of years in the universe.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…2,7 Therefore, the ordered phase of FeNi has drawn renewed attention as a novel alternate to rare earth based permanent magnets. [8][9][10][11] The theoretical maximum magnetic energy product of L1 0 FeNi (∼42 MGOe) is close to that of the currently available best hard magnets. 10,11 It is to be noted that the tetrataenite (L1 0 FeNi phase) was formed during extremely slow cooling of billions of years in the universe.…”
Section: Introductionsupporting
confidence: 71%
“…[8][9][10][11] The theoretical maximum magnetic energy product of L1 0 FeNi (∼42 MGOe) is close to that of the currently available best hard magnets. 10,11 It is to be noted that the tetrataenite (L1 0 FeNi phase) was formed during extremely slow cooling of billions of years in the universe. 8 A brief history of the investigation on tetrataenite has been reviewed in the literature.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…% Ni, near the Fe-rich end of the L1 0 phase field. 13 Our previous studies of NWA 6259 have confirmed via transmission electron microscopy (TEM) the presence of L1 0 FeNi with at least two variants of the c-axis orientation, correlated the intrinsic magnetic properties with the microstructure of bulk tetrataenite, 14 and revealed the extraordinary temperature stability of the magnetic properties. 15 In the latter paper, hard-direction magnetization data were used to estimate the anisotropy field of the NWA 6259 tetrataenite as H a ¼ 20 6 3 kOe, most likely toward the lower end of the range ($17 kOe).…”
mentioning
confidence: 91%
“…Mo k a x-ray diffraction (XRD) and electron back-scatter diffraction (EBSD) were conducted on a polished surface of the cylinder to determine texture and crystallographic orientation, as previously reported. 14 Hysteresis loops were measured using a LakeShore Model 7410 vibrating sample magnetometer (VSM). The large mass of the cylinder proved problematical for magnetic measurements with the VSM; at applied fields greater than 15 kOe, the small magnetic field gradients in the electromagnet caused a deflection of the sample at the end of its mounting rod, creating spurious moment readings.…”
mentioning
confidence: 99%